THE BETTI NUMBERS OF REAL TORIC VARIETIES ASSOCIATED TO WEYL CHAMBERS OF TYPES E7 AND E8 - Choi, Suyoung; Yoon, Younghan; Yu, Seonghyeon (Osaka Journal of Mathematics, 2024)
We compute the rational Betti numbers of the real toric varieties associated to Weyl chambers of types E7 and E8, completing the computations for all types of root systems.